The Impact of Research and Development Investment on Agricultural Sector Performance in Kenya - Kimani, John Githii; Ruigu, Dr. George Ruigu (Journal of Agricultural Policy, 2017)
Purpose: The purpose of the study was to assess the impact of research and development investment/expenditure on the agricultural sector performance in Kenya. Methodology: The study took the peoples impact assessment direction. The data for this study was collected from various government agencies such as KARI, ASTI, Kenya Agricultural Sector Data compendium website, FAOSTAT, World Bank among others. Co-integration and error correction modeling methods were used in analyzing the data for this study. Results: Co-integration results for both the parsimonious and non-parsimonious model indicated that that there is a long-run relationship among the variables in the agriculture performance in Kenya. Further, findings in this study indicated that the variables under study were insignificant determinants of the long run Total Factor Productivity of the agricultural sector. Meanwhile, Trade openness was the only significant determinant of the short run agricultural Total Factor Productivity. Unique Contribution to Policy and Practice: This study recommends the institutionalization of policies aimed at ensuring interaction between the various stakeholders in the agricultural sectors. This interaction will ensure that resources are better allocated to reduce duplication of research and dissemination activities. In addition, greater collaboration among the stakeholders will promote and strengthen the connection between research, policy and the application of research findings. The study further advocates that the government should follow a trade liberazation oriented approach to the agricultural sector as opposed to a trade tightening approach.